KONTRIBUSI GAYA KEPEMIMPINAN WALI KELAS DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS PENGELOLAAN KELAS DI SMP NEGERI KECAMATAN BATHIN SOLAPAN BENGKALIS - Warsini Warsini; Daeng Ayub; M. Jaya Adi Putra (STKIP Pesisir Selatan, 2022)
This study aims to (1) find and analyze how much the homeroom leadership style contributes to the effectiveness of classroom management at the SMP Negeri Bathin Solapan sub-district, Bengkalis, (2) to find and analyze how much organizational culture contributes to the effectiveness of classroom management in public junior high schools. Bathin Solapan District, Bengkalis; (3) To find and analyze how big the contribution of homeroom leadership style and organizational culture to the effectiveness of classroom management at SMP Negeri Bathin Solapan District, Bengkalis.The population in this study amounted to 110 people at 9 State Junior High Schools, the sample/respondent of the study was 87 homeroom teachers in State Junior High Schools in Bathin Solapan District, Bengkalis Regency. Data collection techniques in this study using a questionnaire. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. Processing of data for descriptive statistical analysis in this study using Microsoft Excel and SPSS version 23 for Windows.The research results include; (1) Obtained a significant relationship and a positive contribution of the homeroom leadership style variable (X1) to the effectiveness of classroom management (Y) in public junior high schools in Bathin Solapan District, Bengkalis Regency, (2) Obtained a significant relationship and positive contribution to the variable Organizational Culture (X2) on the Effectiveness of Class Management (Y) in Public Junior High Schools in Bathin Solapan District, Bengkalis Regency, (3) There was a significant relationship and positive contribution of the homeroom leadership style variables (X1) and organizational culture (X2) together on Effectiveness of Class (Y) S Management in Public Junior High Schools in Bathin Solapan District, Bengkalis Regency.